Pancreatic endocrine tissue in benign mediastinal teratoma. - Dunn, P J (1984)
Four cases of benign cystic mediastinal teratoma containing pancreatic tissue have been studied using immunohistochemical and morphometric techniques. The different pancreatic endocrine cell types were stained using antibodies to insulin, glucagon, somatostatin, and pancreatic polypeptide, and the volume density of each cell type was estimated by point counting. Sections from different regions of the normal adult pancreas were also examined and the results compared. There was an increased total volume density of endocrine cells in the teratomatous pancreas, with a pronounced increase in the proportion of somatostatin containing D cells. The results are similar to those described for pancreatic tissue in neonates, and it is suggested that this is further evidence of altered functional differentiation of the pancreatic tissue found in teratomas.